2018
DOI: 10.3389/fmicb.2018.00602
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs in Tuberculosis: New Avenues for Diagnosis and Host-Directed Therapy

Abstract: Tuberculosis (TB) is one of the most fatal infectious diseases and a leading cause of mortality, with 95% of these deaths occurring in developing countries. The causative agent, Mycobacterium tuberculosis (Mtb), has a well-established ability to circumvent the host’s immune system for its intracellular survival. microRNAs (miRNAs) are small, non-coding RNAs having an important function at the post-transcriptional level and are involved in shaping immunity by regulating the repertoire of genes expressed in immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
82
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 165 publications
(189 reference statements)
1
82
1
Order By: Relevance
“…Autophagy is an intracellular process involved in self-digestion or self-eating, in which cytoplasmic components are transmitted to the lysosome and are ultimately degenerated [82]. The pathways associated with autophagy are challenging to regulate at post-transcriptional levels and are well described, but the involvement of miRNAs inactivating or inhibiting autophagy during TB infection is largely unknown [30]. Some reports show the induction of the miR-33 expression in THP-1 and HEK-293 cells, leading to inhibition of pathways involved in autophagy, and also resulting in reprogramming of host lipid metabolism for intracellular survival and TB stability [30].…”
Section: Other Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Autophagy is an intracellular process involved in self-digestion or self-eating, in which cytoplasmic components are transmitted to the lysosome and are ultimately degenerated [82]. The pathways associated with autophagy are challenging to regulate at post-transcriptional levels and are well described, but the involvement of miRNAs inactivating or inhibiting autophagy during TB infection is largely unknown [30]. Some reports show the induction of the miR-33 expression in THP-1 and HEK-293 cells, leading to inhibition of pathways involved in autophagy, and also resulting in reprogramming of host lipid metabolism for intracellular survival and TB stability [30].…”
Section: Other Mirnasmentioning
confidence: 99%
“…MiRNAs are the main regulator of cell differentiation and cell functions, as well as modulators in most cellular functions, including innate and acquired immune systems [27,28]. For example, acquired immune responses, B cell differentiation, antibody production, T cell development, and function are controlled by miRNAs [29], and many studies describe the role of mammalian miRNAs in response to bacterial infections [30]. M. tuberculosis is an intracellular pathogen and can survive within the host macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is estimated that one-third of the world's population is potentially infected. However, it affects about 5-10% of infected people [5].…”
Section: Introductionmentioning
confidence: 99%
“…Because of their high diagnostic potential, open Scientific RepoRtS | (2020) 10:3178 | https://doi.org/10.1038/s41598-020-60132-0www.nature.com/scientificreports www.nature.com/scientificreports/ serum miRNAs have been evaluated as biomarkers in several pathological conditions including TB, with some studies achieving 82% to 100% accuracy in diagnosing TB by evaluating miRNA [13][14][15][16][17][18] . Additionally, several studies have reported differences in miRNA levels among patients with active TB, latent TB, and healthy controls 18,19 . Recently, the roles of miRNAs in mycobacterial infections, particularly in tuberculosis (TB), has received increasing attention 13,20-23 Such studies have reported that specific miRNAs are differentially expressed in macrophages or patients infected with M. tuberculosis complex and that several of these miRNAs interact with their cognate target genes.…”
mentioning
confidence: 99%